Evaluation of anti-diabetic activity of Nishamlaki on streptozotocin induced type II diabetic rats - Jayshree Dawane,; Vijaya A. Pandit,; Swapnil S. Deshpande,; Aniket A. Kuvalekar,; Amruta Mandpe,; Asmita Wele,; Madhuri Dalvi, (International Journal of Phytomedicine, 2014)
Diabetes is a major health problem particularly in India. In spite of many drugs available, uncontrolled diabetes remains a challenge. Moreover, some of the antidiabetic drugs are on the verge of withdrawal due to adverse effects. So, there is an acute need for a new effective and safe drug. Present study was planned to evaluate anti-diabetic efficacy of Nishamalaki in diabetic wistar rats. Nishamalaki was prepared from powder of Curcuma longa and fresh juice of Emblica officinalis according to ayurvedic literature and administered with honey. Diabetes was induced in wistar rats by injection of 60 mg/kg of Streptozotocin and 110 mg/kg Nicotinamide IP. 30 rats showing blood glucose above 250 mg/dl were divided into 5 groups Group I(Control )-Saline, Group II(Control )- Vehicle honey, Group III – Nishamalaki Prophylactic, Group IV- Nishamalaki treatment & Group V- Pioglitazone, given orally for 30 days. Blood glucose levels checked at days 0, 15, 30 & Cholesterol on day 30. Nishamalaki treatment achieved significant (p<0.01) lowering of blood glucose in diabetic rats comparable to that of the Pioglitazone treated group. Nishamalaki also reduced serum cholesterol levels. Antidiabetic efficacy of Nishamalaki in diabetic rats is comparable to Pioglitazone. It has also improved the lipid profile in diabetic rats.